2011
DOI: 10.4236/fns.2011.26088
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Anti-ulcer Activity of Curcumin and Omeprazole during the Acute Phase of Gastric Ulcer—Efficacy of Curcumin in Gastric Ulcer Prevention against Omeprazole

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…That curcumin can prevent and heal gastric ulcers is evident from its dose-dependent effect [5,6]. The curative effect of a curcumin suspension, curcumin raft forming formulation, and lansoprasole on the acetic acid-induced chronic gastric ulcer in rats after 10 days treatment is shown in Table 3.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…That curcumin can prevent and heal gastric ulcers is evident from its dose-dependent effect [5,6]. The curative effect of a curcumin suspension, curcumin raft forming formulation, and lansoprasole on the acetic acid-induced chronic gastric ulcer in rats after 10 days treatment is shown in Table 3.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Curcumin, a polyphenolic compound from the rhizomes of turmeric (Curcuma longa Linn) has been proven to have biological and pharmacological activities such as being an antioxidant, with anti-inflammatory [2], wound healing [3,4] and anti-peptic ulcer abilities [5,6]. Studies of the efficacy of curcumin on acute and chronic gastric ulcer models in rats have demonstrated that curcumin prevented gastric mucosal lesions in a dose dependent manner and accelerated the healing of chronic gastric ulcer with a similar preventive and curative efficacy to a standard antisecretory agent: omeprazole [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Study reported that curcumin and omeprazole showed role in the prevention of gastric lesions development in the gastric wall during the acute phase of gastric ulcer diseases. [ 35 ]…”
Section: Role Of Curcumin In the Diseases Management Described As Folmentioning
confidence: 99%
“…The effects of OMP against gastric mucosal injuries have been thought to depend on its inhibitory action on gastric acid secretion (Kobayashi et al, 2002). However, clinical evaluation of this drug have shown relapse in the long run (Szabo and Vincze, 2000), side effects and drug interactions (Abdul-Aziz, 2011). This has been rational for the development of innovative drug that reduces the offensive factors and is proved to be safe, clinically effective, having better patient tolerance, relatively less expensive and globally competitive.…”
Section: Introductionmentioning
confidence: 99%